Modulating single-molecule magnet behaviors of Dy4III clusters through utilizing two different β-diketonate coligands. (1st March 2019) - Xu, Chun Ying; Qiao, Xin-Yi; Tan, Yu; Liu, Su-Su; Hou, Wen-Ying; Cui, Ying-Ying; Wu, Wei-Long; Hua, Yu-Peng; Wang, Wen-Min
Graphical abstract: Two rhombus-shaped Dy4 clusters with similar structures have been obtained. Magnetic analysis revealed different single-molecule magnet (SMM) behaviors occurs in1 and2, which originated from the two slightly different β-diketonate (Htmhd and Hacac). Abstract: In search of simple approaches to rationally modulate the single-molecule magnet behaviors in polynuclear lanthanide clusters, a new system containing two structurally closely related rhombus-shaped Dy4 clusters, Dy4 (tmhd)4 L6 ( μ 3 -OH)2 ·5CH3 CN (1 ) and Dy4 (acac)4 L6 ( μ 3 -OH)2 (2 ) (HL = 5-(4-ethyoxylbenzylidene)-8-hydroxylquinoline, Htmhd = 2, 2, 6, 6-tetramethyl-3, 5-heptanedione and Hacac = acetylacetonate), have been obtained by employing two dysprosium β-diketonate salts to react with a bidentate Schiff base ligand (HL). The two Dy4 clusters have similar structures and possess a structure in which four Dy 3+ ions remain in a perfect plane with a rhombus-shaped geometric construction. Dynamic magnetic analysis revealed different single-molecule magnet (SMM) behaviors occurs in1 and2 . Under zero direct-current (dc) field, 1 displays typical SMMs behavior with Δ E / k B  = 39.6 K and τ 0  = 2.1 × 10 −6  s. However, for2, a peculiar feature of the χ ″ versus temperature curves is that more than two peaks that are frequency-dependent are revealed, indicating the occurrence of multifold relaxation processes that lead to two Δ E / k B (31.3 K and 81.6 K) and pre-exponential factors ( τ 0  = 3.1 × 10 −6  s, τ 0  = 2.2 × 10 −7  s).